2014
DOI: 10.1080/03057925.2014.884919
|View full text |Cite
|
Sign up to set email alerts
|

Contextualising the career pathways of women principals in Hong Kong: a critical examination

Abstract: The fields of gender and educational leadership have been enriched recently by analyses of national case studies from non-western contexts. By contextualising women's career development, these studies highlight the importance of including experiences other than those generated from Anglo-American-Australian contexts, thus broadening our knowledge base for more nuanced theorisation in the field. This paper contributes a close examination of the career histories of eight female primary school principals in Hong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(25 reference statements)
0
7
0
2
Order By: Relevance
“…Earlier research studies tend to blame women's deficiencies and orientation for their underrepresentation (Hoyle 1969) or according to later research that women are said to lack confidence (Hoff & Mitchell, 2008;Young & McLeod, 2001) or lack motivation (Kaparou & Bush, 2007). Chan, Ngai & Choi ( 2016) discuss other factors and found out that family orientation overweighs career orientation. They (ibid.)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Earlier research studies tend to blame women's deficiencies and orientation for their underrepresentation (Hoyle 1969) or according to later research that women are said to lack confidence (Hoff & Mitchell, 2008;Young & McLeod, 2001) or lack motivation (Kaparou & Bush, 2007). Chan, Ngai & Choi ( 2016) discuss other factors and found out that family orientation overweighs career orientation. They (ibid.)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For female principals to break this glass ceiling, they need to invoke and exercise their agency. As Chan et al (2016) notes, almost total absence of formal institutional support implies that women have to turn to their own means (agency) and bear personal costs when pursuing career progression.…”
Section: Receipt Of Female Principals By Educators and Smt Members Atmentioning
confidence: 99%
“…In can be concluded that traditional stereotypes in the SMT structure were the major cause of rejection of female principals in these schools. As Chan et al (2016) argue, when gender norms in society prescribe different, and often inferior, roles to women, these shape the way schools are organised and the social perception of leadership. "Sexism tends to prevail when the school management or selection committee is dominated by men, who are more likely to hire and promote other men who look, think and act like them."…”
Section: Receipt Of Female Principals By Educators and Smt Members Atmentioning
confidence: 99%
“…Following this, Sanderson and Whitehead (2016) determined that women had a lack of confidence when they were promoted to the position of school principal. Yet Chan et al (2016) note that a sense of guilt amongst women is often the reason why women do not consider leadership positions and retire prematurely. In addition, Chan et al (2016:208) suggest that women should be encouraged and given the necessary support, especially from senior staff, to seize opportunities for promotion.…”
Section: Managementmentioning
confidence: 99%